Gakkel Ridge Major Elements RPI - Langmuir, Charles (IEDA: EarthChem Library, 2011)
Abstract: The data set contains major oxide data for MORB glasses from the Gakkel Ridge collected on the HY0102 and PS59 cruises, measured at RPI by microprobe.